مستوى تقدير الذات لدى المعاقين حركيا الممارسين للنشاط الرياضي - خوجة, عادل; بن عمر, مراد; زحاف, محمد (Université de M'sila, 2018)
الملخص: يهدف البحث التعرف إلى مستوى تقدير الذات لدى الرياضيين المعاقين حركيا وكذا هل توجود فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى المعاقين حركيا الممارسين للنشاط الرياضي تعزى إلى متغيرة (السن، الجنس، نوع الإعاقة، سبب الإعاقة، المستوى التعليمي، الخبرة في اللعب، ونوع الرياضة)، وتم استخدام المنهج الوصفي، على عينة تكونت من (21) معاقا حركيا يمارسون كرة السلة على الكراسي المتحركة وألعاب القوى من الجنسين والذين يبلغون (14-19 سنة) تم اختيارهم بالطريقة العمدية عن طريق الرابطة الولائية لرياضة المعاقين لولاية المسيلة، واستخدم الباحثون مقياس تقدير الذات لـ روزنبيرج (Rosenberg, 1965) كأداة للقياس، وقد أشارت نتائج البحث إلى: مستوى تقدير الذات مرتفع لدى المعاقين حركيا الممارسين للنشاط الرياضي، وتوجد فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى المعاقين حركيا الممارسين للنشاط الرياضي تعزى إلى متغيرة (السن، الجنس، نوع الإعاقة، المستوى التعليمي، ونوع الرياضة)، كما لا توجد فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى المعاقين حركيا الممارسين للنشاط الرياضي تعزى إلى متغيرة (طبيعة الإعاقة، الخبرة في اللعب). - Abstract: The research aims at identifying the level of self-esteem in persons with physical disabilities practicing sports activities and if there are statically significant differences to the level of self-esteem in persons with physical disabilities practicing sports activities due to the variable (age, sex, type of handicap, cause of disability, educational level, gaming experience, Kind of sport). Researchers have used the Descriptive method on a sample composed of 21 disabled persons (Girls and Boys) from 14 to 19 years. Practicing sports activities selected by the purposive method via the Province League of the Disabled Sports of the Province of M'sila, Researchers have used the measure of self-esteem prepared by (Rosenberg, 1965) as a measuring tool. The results of the research indicated: The level of self-esteem is increasing in persons with physical disabilities practicing sports activities. The existence of statistically significant differences in the level of self-esteem in persons with physical disabilities practicing sports activities due to the variable (age, sex, type of handicap, educational level, Kind of sport). There are no statistically significant differences in the level of self-esteem in persons with physical disabilities practicing sports activities due to the variable (cause of disability, gaming experience).
Keywords: تقدير الذات، الإعاقة الحركية، النشاط الرياضي. self-esteem, physical disabilities, sports activities.